(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Article is devoted to a problem of formation of national idea of the people, the state. In it the humanitarian discourse of the president of the Republic of Kazakhstan N.A. Nazarbayev, in particular his book «World Epicentre» (2001) is considered. In this regard such terms and their major importances as the nation, ethnos, national idea, a humanitarian discourse, etc. are studied. Article purpose – to show on material of the publicistic text as the national idea of the Kazakh people arose, in general the sovereign state of the RK. As illustrative material fragments from the specified book of the Leader of the nation in which information on the termination of tests of the nuclear weapon in the territory of RK and refusal (1991-1999) of it is in detail stated are represented. For achievement of a research objective, complex selection from of the text of individual author’s maxims, their description and systematization were used. Results of the analysis can be used on classes in the lingvostilistic analysis of a humanitarian discourse for students and undergraduates of philological specialists.